All solution-processed micro-structured flexible electrodes for low-cost light-emitting pressure sensors fabrication - Rie Shimotsu (Nature Portfolio, 2017)
Abstract Recent studies have demonstrated the advantage of developing pressure-sensitive devices with light-emitting properties for direct visualization of pressure distribution, potential application to next generation touch panels and human-machine interfaces. To ensure that this technology is available to everyone, its production cost should be kept as low as possible. Here, simple device concepts, namely, pressure sensitive flexible hybrid electrodes and OLED architecture, are used to produce low-cost resistive or light-emitting pressure sensors. Additionally, integrating solution-processed self-assembled micro-structures into the flexible hybrid electrodes composed of an elastomer and conductive materials results in enhanced device performances either in terms of pressure or spatial distribution sensitivity. For instance, based on the pressure applied, the measured values for the resistances of pressure sensors range from a few MΩ down to 500 Ω. On the other hand, unlike their evaporated equivalents, the combination of solution-processed flexible electrodes with an inverted OLED architectures display bright green emission when a pressure over 200 kPa is applied. At a bias of 3 V, their luminance can be tuned by applying a higher pressure of 500 kPa. Consequently, features such as fingernails and fingertips can be clearly distinguished from one another in these long-lasting low-cost devices.